2012
DOI: 10.1002/cphc.201100729
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Scanning Transmission Electron Microscopy (HRSTEM) Techniques: High‐Resolution Imaging and Spectroscopy Side by Side

Abstract: This work presents an overview of high-resolution scanning transmission electron microscopy (HRSTEM) techniques and exemplifies the novel quantitative characterization possibilities that have emerged from recent advances in these methods. The synergistic combination of atomic resolution imaging and spectroscopy provided by HRSTEM is highlighted as a unique feature that can provide a comprehensive analytical description of material properties at the nanoscale. State-of-the-art high-angle annular dark field and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…The presence and the distribution of doping elements have an important effect on the morphology and structure, which can induce a change in the surface energy and, consequently, in the crystal growth mechanism. 31,33 In fact, from the results reported here, V (as the dopant) plays a significant role in the crystal growth mechanism, which is very important to obtain doped nanostructures with altered shapes.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The presence and the distribution of doping elements have an important effect on the morphology and structure, which can induce a change in the surface energy and, consequently, in the crystal growth mechanism. 31,33 In fact, from the results reported here, V (as the dopant) plays a significant role in the crystal growth mechanism, which is very important to obtain doped nanostructures with altered shapes.…”
Section: Resultsmentioning
confidence: 75%
“…14,[24][25][26][27][28][29][30] Furthermore, the presence and distribution of the doping elements in the nanostructures can result in a different crystal growth mechanism, influencing the final shape of the nanoparticles. [24][25][26][31][32][33] In all of these cases, a controllable and simple synthesis process is required to achieve these goals. Recently, several studies have reported the synthesis of diverse nanostructures through the hydrothermal treatment of the peroxo-metal complex, which is considered a simple and environmentally friendly method to obtain nanostructures without contaminants like halide ions or organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…To find the explanation for the protectiveness of scales formed in different solutions, combined FIB/TEM/EDS analyses were conducted on 5Cr specimens pretreated in ‘DDS only’ solution, ‘DDS + NAP’ solution, and ‘NAP only’ solutions. The scales formed in these three solutions are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to obtaining and processing images,o ther common techniques in STEM are energyd ispersive X-ray (EDX)s pectroscopy,e lectron energyl oss spectroscopy( EELS), and STEM tomography, some of them even in environmental mode. [50,51] Tomography can be usedf or the determination of the facets;o ne striking example of the capabilities of this techniquei st he obtainability of gold nanorodst omograms at atomic resolution to solvet heir facets and structure (Figures 3c, 3d). [9] Thes ame techniquec an be extended, combined with EDXS,a llowingc ompositional tomograms with spatial atomic resolution.…”
Section: Characterization Techniquesmentioning
confidence: 99%